Implementation of Authentic Assessment in Historical Learning in Madrasah Aliyah Negeri (MAN) Pekanbaru City - Zulfa Hendri; Kurniawati Kurniawati; Umasih Umasih; Jufrianis Jufrianis (LPPM of NAROTAMA UNIVERSITY, 2020)
Purpose: The purpose of this study was to determine how the implementation of authentic assessment in history learning at Madrasah Aliyah Negeri (MAN) 1 and MAN 4 Pekanbaru City. Design/methodology/approach: The research method used is a qualitative case study. A research location is in MAN 1 and MAN 4 Pekanbaru City. Sources of data in this study were informants, namely the principal, vice principal in the field of curriculum, teachers and students, learning activities and documents. Data collection techniques using interview methods, documentation study, questionnaires and observations. Findings: The results of this study indicate that history teachers have a good understanding of authentic assessment in the 2013 curriculum in MAN 1 and MAN 4, Pekanbaru City, history teachers have carried out knowledge assessments and skills assessments well, while in terms of analysis and reporting of authentic teacher assessment results using processing software online scores; The obstacles experienced by history teachers are the plurality of students with different backgrounds and characters, while the factors that support teachers in implementing authentic assessments are quality students, the availability of facilities and learning resources and the existence of value processing software. Practical implications: Result of this study can be used as reference in implementation of Authentic Assessment of any subject. Originality/value: This research is original because there is no similar research that been conducted in MAN Pekanbaru City. Paper type: Research paper